Threats of force : international law and strategy - Grimal, Francis (London ; New York : Routledge, 2013)
"Despite recent attempts by scholars to examine the absolute prohibition of threats of force under Article 2(4) of the UN Charter, threats remain a largely un-chartered area in international law when compared with actual uses of force. Adopting an interdisciplinary approach and drawing on the works of strategic literature and international relations theory, this book examines the theoretical nature behind a threat of force in order to inform and explain why and how the normative structure operates in the way it does. The core of the book addresses whether Article 2(4) is adequately suited to the current international climate and, if not, whether an alternative means of rethinking Article 2(4) would provide a better solution. Francis Grimal also addresses two other fundamental issues within the realm of threats of force that remain largely unexplored in present literature. Firstly, the interrelationship between threats of force and self-defence, would a state have to suffer an armed attack before threatening force in self-defence or could it threaten force pre-emptively? Can a state lawfully use a threat of force as a means of self-defence rather than force under the present Charter system? Finally, the book explores the point at which a state pursuing nuclear capabilities may breach Article 2(4) with particular reference to both North Korean and Iranian efforts to pursue nuclear technology.This topical book will be of great interest not only to scholars and postgraduates in international law but also to academics and students across several fields due to its interdisciplinary approach including strategic studies and international relations theories."--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: United Nations; Ultimatums (International relations); Aggression (International law); Pacific settlement of international disputes; Electronic books